The Bad-Tempered Ladybird - Carle, Eric. (London : Puffin Books, 2010)
A grouchy ladybug who is looking for a fight challenges everyone she meets regardless of their size or strength.
2.7
K-3.
K-3
Keywords: Ladybugs -- Fiction; Ladybugs -- Fiction